2023
DOI: 10.1177/00037028231199772
|View full text |Cite
|
Sign up to set email alerts
|

Application of Infrared and Near-Infrared Microspectroscopy to Microplastic Human Exposure Measurements

Stephanie Wright,
Joseph Levermore,
Yukari Ishikawa

Abstract: Microplastic pollution is a global issue for the environment and human health. The potential for human exposure to microplastic through drinking water, dust, food, and air raises concern, since experimental in vitro and in vivo toxicology studies suggest there is a level of hazard associated with high microplastic concentrations. However, to infer the likelihood of hazards manifesting in the human population, a robust understanding of exposure concentrations is needed. Infrared and near-infrared microspectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 107 publications
0
3
0
Order By: Relevance
“…The 24 water samples (3 from each location) underwent filtration using glass fiber filter papers, followed by digestion with 50 ml of hydrogen peroxide, and were agitated for a period of 5 days, as outlined by Wright et al [ 21 ]. Subsequently, the digested materials were transferred into a separating funnel containing an aqueous potassium formate solution.…”
Section: Methodsmentioning
confidence: 99%
“…The 24 water samples (3 from each location) underwent filtration using glass fiber filter papers, followed by digestion with 50 ml of hydrogen peroxide, and were agitated for a period of 5 days, as outlined by Wright et al [ 21 ]. Subsequently, the digested materials were transferred into a separating funnel containing an aqueous potassium formate solution.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that techniques of infrared spectroscopy have molecular sensitivity comparable to that of immunohistochemistry (IHC) in detecting biochemical changes in biological samples, and require less material, less effort, and are faster and cheaper . Infrared spectroscopy can be used to detect the particle size distribution of microplastics in tissues, biofluids and living environments, and to understand the risk levels of these exposures to humans . At present, ATR-FTIR spectroscopy has been widely used to understand changes in cells and tissues, especially those changes caused by exposure to environmental disrupting chemicals (EDCs), due to its ability to identify specific chemical changes in biological samples .…”
Section: Introductionmentioning
confidence: 99%
“… 16 Infrared spectroscopy can be used to detect the particle size distribution of microplastics in tissues, biofluids and living environments, and to understand the risk levels of these exposures to humans. 17 At present, ATR-FTIR spectroscopy has been widely used to understand changes in cells and tissues, especially those changes caused by exposure to environmental disrupting chemicals (EDCs), due to its ability to identify specific chemical changes in biological samples. 18 ATR-FTIR spectroscopy has been widely used in environmental toxicology studies, mainly for identifying the toxic effects of pollutants and exploring the mechanisms of toxic effects.…”
Section: Introductionmentioning
confidence: 99%